Hygiene and biosecurity: the language and politics of risk in an era of emerging infectious diseases - Brown, Brian; Nerlich, Brigitte; Crawford, Paul; Koteyko, Nelya; Carter, Ronald (Wiley, 2009)
Infectious diseases, such as methicillin-resistant Staphylococcus aureus and avian influenza, have recently been high on the agenda of policy makers and the public. Although hygiene and biosecurity are preferred options for disease management, policy makers have become increasingly aware of the critical role that communication assumes in protecting people during outbreaks and epidemics. This article makes the case for a language-based approach to understanding the public perception of disease. Health language research carried out by the authors, based on metaphor analysis and corpus linguistics, has shown that concepts of journeys, pathways, thresholds, boundaries and barriers have emerged as principal framing devices used by stakeholders to advocate a hygiene based risk and disease management. These framings provide a common ground for debate, but lead to quite different perceptions and practices. This in turn might be a barrier to global disease management in a modern world.